Devkota’s Worldview: A Philosophical Analysis of Laxmi Nibandha Sangraha - Phuyal, Komal Prasad (Bodhi: An Interdisciplinary Journal, 2024)
Pioneer modern voice in Nepali literature, Laxmi Prasad Devkota (1909–1959), places both Nepal and Nepali ways of life at the center in his essays that reflect on both the contemporary Nepali practices of his time and seek to identify the ways to address the lapses in the ethos of his time. As a modern Nepali essayist, he carries the voice of the 1920s and 1930s national awakening in his collection of essays titled Laxmi Nibandha Sangraha [Laxmi Collection of Essays] (1942–1943). All his thirty-seven essays present his reflection on his self, society, and the awakening of the nation. Often, Devkota takes a very vicarious road to the subject matter and hides the argument in his aesthetic ways of presenting the social reality: his harsh commentary on social development also finds due space in what he finds relevant to talk about the limits to the social and the political in his time. The modern essayist loves his people and his culture: he celebrates the ways of his people and his society, seeking out the strengths of his own culture and exposing the weaknesses of the imported set of values. The reading of his essays also reveals his ambivalent attitude toward what he sees in the world, in that he stands to denounce and appreciate specific values of the modern world, thereby letting himself stand in a much undecided intellectual mood as well. This paper discusses the worldview that Devkota has developed in his essays in Laxmi Nibandha Sangraha.